Strategic adaptation & collaboration : European global banks approach to Fintech - Gandara, Dino Mejia (2018)
Banks are today challenged by new entrants to their industry mainly regarded as Financial Technology (Fintech) Companies. Fintech companies are rather innovative and offer great customer experience while being very much customer oriented. This apparent threat demands banks to deal with both new technologies and evermore demanding customers. The environmental shock caused by Fintech companies in the European and global landscape is very much felt across the industry and shifts the way business has been traditionally carried for the last years since they create new business models and take away customers from existing banking services. All this upheaval raised the question on “How are European global banks reacting to the emergence of Fintech companies?” To answer this, it was necessary to look into concrete actions towards innovation that banks are taking, which methodologies for innovation and collaboration are being adopted and who are they engaging with in such activities. This thesis was built upon literature around strategic management and entrepreneurship and later taking an overview on the innovation landscape of 18 European Global Banks from the years 2012 to 2018 regarding their approaches to strategic adaptation, innovation mindset and collaboration. Public documentation provided online by banks was the main sources for exploration to finding relevant information. The collected data provided an overview on the different initiatives that European banks have considered relevant in their journey of strategic adaptation and transformation. The findings show that banks are going through an organizational transformation and are intending to increase their collaboration and innovation capabilities. Some of the carried collaboration initiatives included engaging in a partnership with Fintech companies, other banks, innovation experts and players outside the industry. Regarding entrepreneurship initiatives, banks hosted accelerators, incubation programs, and hackathons, started innovation oriented venture funds and organized knowledge sharing events for internal and external stakeholders. Focusing on strategic adaptation, an innovation mind-set and collaborative entrepreneurship provide today an opportunity for banks to reinvent them-selves in the areas that need attention.